Central Obesity Is Associated with Variations in TSH and ACTH Levels among Euthyroid Obese Individuals - Difei Lu; Zhenfang Yuan; Ying Gao; Wei Liu; Junqing Zhang (International Journal of Endocrinology)
Introduction. The interactions of central obesity and body composition with thyroid hormones and the hypothalamus-pituitary-adrenal (HPA) axis are unclear; both central obesity and body composition have an impact on energy homeostasis. Our study aimed to investigate the association between body composition and pituitary hormones, including the HPA axis and pituitary-thyroid axis, in a Chinese population of euthyroid overweight and obese individuals. Methods. This was a cross-sectional study. Overweight and obese patients who regularly visited the multidisciplinary team (MDT) for obesity at Peking University First Hospital were enrolled in the study. Thyroid function, morning serum ACTH and cortisol levels, thyroid peroxidase antibody (TPOAb), thyroglobulin antibody (TgAb), body composition, and metabolic indicators, including liver function and the lipid profile, were measured at the first visit. Statistical analysis was performed using SPSS version 21.0 (IBM, USA). Results. In total, 441 patients with overweight or obesity were enrolled (male/female, 123/318). Patients were assigned to four groups according to the thyroid-stimulating hormone (TSH) level stratified by quartiles, and increased body mass index (BMI) was revealed in the highest TSH quartile group (p=0.002). Hip circumference (HC) of patients in the highest TSH quartile group was significantly increased (p=0.021). Morning ACTH levels and fasting insulin levels were significantly elevated in patients in the highest TSH quartile group (p=0.027 for fasting insulin, p<0.001 for ACTH). In the female subgroup, patients in the highest TSH quartile group showed increases in BMI (p=0.010), waist circumference (WC) (p=0.007), muscle mass of the lower extremities (p=0.020), fasting C-peptide (p=0.031), and ACTH (p=0.002). In the male subgroup, patients in the highest TSH quartile group exhibited higher BMI (p=0.017), HC (p=0.036), and ACTH (p=0.003). Among patients in the highest ACTH quartile group, there was an elevated proportion of males (p=0.003), and FT3 (p=0.005), fasting insulin (p=0.037), and cortisol (p<0.001) levels were increased. Weight (p<0.001), BMI (p<0.001), WC (p<0.001), HC (p<0.001), muscle mass of the upper extremities (p=0.003), muscle mass of the lower extremities (p=0.005), and total muscle mass (p=0.003) were elevated in patients in the highest ACTH quartile group. HC was found to be an independent factor after adjustment for other confounders and was positively associated with the TSH level (p=0.004 for the regression model, B = 0.152, p=0.004). Conclusions. BMI is positively correlated with TSH and ACTH levels in both male and female obese individuals. The ACTH level was positively associated with male sex and increased BMI and muscle mass. Hip circumference was an independent factor that was positively related to TSH levels.